ISOLASI SENYAWA KUMARIN DARI KULIT BATANG KECAPI (Sandoricum koetjape) SEBAGAI ANTIBAKTERI - FEBRIA ELVY SUSANTI (LLDIKTI Wilayah X, 2016)
Isolation of coumarine on stem bark from Sandoricum koetjape has done. Stem bark powder were extracted by maceration method using organic solvents hexane, ethyl acetate and methanol. Extract of ethyl acetate was separated by column chromatography. The antibacterial activities of extracts made by method of diffusion discs. The results showed the extracts of ethyl acetate has the highest activity than others with 12 mm (Staphylococcus aureus) and 19 mm (Escherichia coli) inhibitory area. Isolation result is needle white crystals from extracts of ethyl acetate with melting point 194ÂºC - 195ÂºC.